Nicotine preloading for smoking cessation: the Preloading RCT - Aveyard, P; Lindson, N; Tearne, S; Adams, R; Ahmed, K; Alekna, R; Banting, M; Healy, M; Khan, S; Rai, G; Wood, C; Anderson, E; et al. (National Coordinating Centre for Health Technology Assessment, 2018)
Background Nicotine preloading means using nicotine replacement therapy prior to a quit date while smoking normally. The aim is to reduce the drive to smoke, thereby reducing cravings for smoking after quit day, which are the main cause of early relapse. A prior systematic review showed inconclusive and heterogeneous evidence that preloading was effective and little evidence of the mechanism of action, with no cost-effectiveness data. Objectives To assess (1) the effectiveness, safety and tolerability of nicotine preloading in a routine NHS setting relative to usual care, (2) the mechanisms of the action of preloading and (3) the cost-effectiveness of preloading. Design Open-label randomised controlled trial with examination of mediation and a cost-effectiveness analysis. Setting NHS smoking cessation clinics. Participants People seeking help to stop smoking. Interventions Nicotine preloading comprised wearing a 21 mg/24 hour nicotine patch for 4 weeks prior to quit date. In addition, minimal behavioural support was provided to explain the intervention rationale and to support adherence. In the comparator group, participants received equivalent behavioural support. Randomisation was stratified by centre and concealed from investigators. Main outcome measures The primary outcome was 6-month prolonged abstinence assessed using the Russell Standard. The secondary outcomes were 4-week and 12-month abstinence. Adverse events (AEs) were assessed from baseline to 1 week after quit day. In a planned analysis, we adjusted for the use of varenicline (Champix®; Pfizer Inc., New York, NY, USA) as post-cessation medication. Cost-effectiveness analysis took a health-service perspective. The within-trial analysis assessed health-service costs during the 13 months of trial enrolment relative to the previous 6 months comparing trial arms. The base case was based on multiple imputation for missing cost data. We modelled long-term health outcomes of smoking-related diseases using the European-study on Quantifying Utility of Investment in Protection from Tobacco (EQUIPT) model. Results In total, 1792 people were eligible and were enrolled in the study, with 893 randomised to the control group and 899 randomised to the intervention group. In the intervention group, 49 (5.5%) people discontinued preloading prematurely and most others used it daily. The primary outcome, biochemically validated 6-month abstinence, was achieved by 157 (17.5%) people in the intervention group and 129 (14.4%) people in the control group, a difference of 3.02 percentage points [95% confidence interval (CI) –0.37 to 6.41 percentage points; odds ratio (OR) 1.25, 95% CI 0.97 to 1.62; p = 0.081]. Adjusted for use of post-quit day varenicline, the OR was 1.34 (95% CI 1.03 to 1.73; p = 0.028). Secondary abstinence outcomes were similar. The OR for the occurrence of serious AEs was 1.12 (95% CI 0.42 to 3.03). Moderate-severity nausea occurred in an additional 4% of the preloading group compared with the control group. There was evidence that reduced urges to smoke and reduced smoke inhalation mediated the effect of preloading on abstinence. The incremental cost-effectiveness ratio at the 6-month follow-up for preloading relative to control was £710 (95% CI –£13,674 to £23,205), but preloading was dominant at 12 months and in the long term, with an 80% probability that it is cost saving. Limitations The open-label design could partially account for the mediation results. Outcome assessment could not be blinded but was biochemically verified. Conclusions Use of nicotine-patch preloading for 4 weeks prior to attempting to stop smoking can increase the proportion of people who stop successfully, but its benefit is undermined because it reduces the use of varenicline after preloading. If this latter effect could be overcome, then nicotine preloading appears to improve health and reduce health-service costs in the long term. Future work should determine how to ensure that people using nicotine preloading opt to use varenicline as cessation medication. Trial registration Current Controlled Trials ISRCTN33031001.